REPRODUCTIVE PARAMETERS FOLLOWING ESTRUS SYNCHRONIZATION OF SANGAMNERI AND OSMANABADI GOATS - AMLE, M B; BIRADE, H S; GULAWANE, S U (The Indian Journal of Animal Reproduction, 2022)
Sangamneri (n=11) and Osmanabadi (n=7) breed goats (age, 2-4 yr; BW, 22-28 kg) subjected to estrussynchronization protocol (progestagen-impregnated intra-vaginal sponge for 7 days + Inj. eCG i.m. on the day ofsponge removal) exhibited 100% estrus response with an earlier onset of estrus in Sangamneri breed (46.9± 2.5vs. 24±6.23 h, p
Keywords: Estrus synchronization; Intra-vaginal sponges; Osmanabadi goat; Reproduction; Sangamneri goat